Voluntary wheel running reduces tumor growth and increases capillarity in the heart during doxorubicin chemotherapy in a murine model of breast cancer - Uurasmaa, Tytti-Maria; Ricardo, Chloé; Autio, Anu; Heinonen, Ilkka H. A.; Rundqvist, Helene; Anttila, Katja (Frontiers in Physiology, 2024)
The possible beneficial effects of physical activity during doxorubicin treatment of breast cancer need further investigation as many of the existing studies have been done on non-tumor bearing models. Therefore, in this study we aim to assess whether short-term voluntary wheel-running exercise during doxorubicin treatment of breast-cancer bearing mice could induce beneficial cardiac effects and enhance chemotherapy efficacy. Murine breast cancer I3TC-cells were inoculated subcutaneously to the flank of female FVB-mice (n=16) that were divided to exercised and nonexercised groups. Two weeks later doxorubicin treatment was started via intraperitoneal administration (5mg/kg weekly, for three weeks). Organs were harvested a day after the last dose. The tumor volume overtime was significantly affected by group, exercising group having lower tumor volumes. The exercised group had increased bodyweight gain, tumor apoptosis, capillaries per cardiomyocytes and cardiac lactate dehydrogenase activity compared to the un-exercised group, but tumor blood vessel density and maturation, and tumor and cardiac HIF1-α and VEGF-A levels did not differ from non-exercised group. We conclude that even short-term light exercise such as voluntary wheel running exercise can diminish subcutaneous mammary tumor growth, possibly partly via increased tumor apoptosis, and increase cardiac capillaries per cardiomyocytes during doxorubicin treatment with beneficial effect on bodyweight, which may have positive effects on cancer treatment outcomes.